2012
DOI: 10.1007/s10459-012-9363-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding self-assessment as an informed process: residents’ use of external information for self-assessment of performance in simulated resuscitations

Abstract: Self-directed learning requires self-assessment of learning needs and performance, a complex process that requires collecting and interpreting data from various sources. Learners' approaches to self-assessment likely vary depending on the learner and the context. The aim of this study was to gain insight into how learners process external information and apply their interpretation of this information to their self-assessment and learning during a structured educational activity. The study combined quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…However, there is potential concern about whether self-assessment using milestones will help to inform resident progress or to facilitate self-directed learning skills. Research over the past decade has shown that selfassessment may encourage some residents to improve their awareness of deficiencies, create individualized learning plans, and bolster specific knowledge areas [4][5][6][7][8][9]. Unfortunately, self-assessment is fraught with inaccuracy and varies depending on the setting, content, and learner perspective [10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is potential concern about whether self-assessment using milestones will help to inform resident progress or to facilitate self-directed learning skills. Research over the past decade has shown that selfassessment may encourage some residents to improve their awareness of deficiencies, create individualized learning plans, and bolster specific knowledge areas [4][5][6][7][8][9]. Unfortunately, self-assessment is fraught with inaccuracy and varies depending on the setting, content, and learner perspective [10][11][12].…”
mentioning
confidence: 99%
“…To our knowledge, this is not a common practice in the milestone-based assessment era. Prior studies looking at this type of informed self-assessment (providing residents with external feedback for the sake of synthesizing assessments) have found that it minimizes the flaws inherent in primary self-assessment reliability while capturing the value of learner investment in the assessment process [5,7,23].…”
mentioning
confidence: 99%
“…Although it is known from previous studies that self-assessment requires clear, timely, specific and constructive feedback to inform the learners' self-assessment (Sargeant et al 2010); not much is known about the conditions under which self-assessment is effective and does enhance learning. Plant et al (2012) report an interesting study about the process of self-assessment. The aim of the study was to better understand HOW and WHY resident physicians adjust their self-assessment after reviewing their own performance in leading a simulated resuscitation in the presence of an interviewer.…”
mentioning
confidence: 99%
“…So, whether self-assessment can improve learning cannot be answered based on the study of Plant et al (2012) as the authors also mention in their discussion. Nevertheless, this study demonstrates that qualitative feedback is crucial but also that dialogue, either in a group or with a personal coach, stimulates reflections.…”
mentioning
confidence: 99%
“…
Authors replyThe authors would like to thank Dr. Dolmans for her thoughtful commentary on our study examining residents' use of external information during self-assessment of their performance (Plant et al 2012).In her piece entitled ''Self-assessment and dialogue: can it improve learning? '', Dr. Dolmans (2012) discusses the importance of dialogue in the self-assessment process.
…”
mentioning
confidence: 99%